Pyroelectric USB-joulemeters of pulsed laser radiation - Samoylov, V.B.; Levash, L.V.; Rosnovskiy, O.A.; Vedula, M.Yu.; Rad'ko, V.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
The general arrangement, principle of operation, and basic parameters of pyroelectric USB-meters of energy of pulsed laser radiation have been described. A smart head of the meter converts the signal from the pyroelectric sensor and immediately transfers it to the PC using a high-speed USB 2.0 connection. The device consists of two circuit panels located in the common package. The pyroelectric sensitive element and preamplifier are mounted on the sensor panel. The output of the preamplifier is connected to the input of the preliminary digital processing panel. The meter is connected to a host computer that performs further processing, storage, and monitoring of data. The sensor panel can be produced in two modifications, depending on the pulse energy. Sensitive elements on the base of LiNbO₃ or LiTaO₃ with absorbing coatings are used for measuring the low-energy pulses, whereas the transparent sensitive elements with a small intrinsic absorption are used for measurements of high-energy radiation pulses. The pulse rate and pulse energy can vary from single pulses up to 2 kHz and from 0.1 µJ up to 0.5 J, respectively.